Nutrition care for chronic disease-related malnutrition in patients with abdominal tumor comorbidities - Deri Andika Putra; ‘Ainil Mardhiyah (PT WIM Solusi Prima, 2026)
Abdominal tumor is a serious medical condition that can impair food intake and lead to severe malnutrition. Inadequate oral intake due to abdominal pain, nausea, and pre- and post-operative conditions significantly contributes to nutritional status deterioration. To report the implementation of standardized nutrition care process in a patient with abdominal tumor presenting with inadequate oral intake and severe malnutrition due to chronic disease. A case study was conducted over 4 days of observation (August 6–9, 2024) at the Teratai Ward, Prof. Dr. Margono Soekarjo Hospital, Purwokerto. Data were collected through comprehensive nutritional assessment including anthropometric, biochemical, physical/clinical, and dietary history using SQ-FFQ and 24-hour recall. Nutritional interventions included stepwise diet progression (liquid, strained, soft), education, counseling, and team coordination. Daily monitoring of food intake, clinical/physical findings, and anthropometry was performed. Mrs. S (63 years old) had severely underweight nutritional status (BMI 16.6 kg/m²) with 11.1% weight loss over 3 months. Initial recall showed only 35.8% of energy requirements were met. Following 4 days of nutritional intervention, intake improved significantly to 80.9% energy and 98.5% protein on day 4. Body weight was maintained at 40 kg with no further loss. A comprehensive standardized nutrition care process was effective in progressively improving food intake and preventing further weight loss in a post-laparotomy abdominal tumor patient.